Analysis Of Foreign Economic Relations Of The Agricultural System Of The Kashkadarya Region - Head teacher., Rasulova Muxabbat Tishabayevna; Assistant., Normurodov Sarvar Norboy o’g’li (Genius Journals, 2024)
This article presents the analysis of the prospects for production in dekhkan farms of the Kashkadaryа region. It also presents a set of econometric models and forecasts of livestock and crop production indicators in dekhkan farms and household plots. The analysis of foreign economic relations of the agricultural system is presented in tables and diagrams.
Keywords: Dekhkan farms; owners of growing and livestock production; production